2022
DOI: 10.1371/journal.pone.0264909
|View full text |Cite
|
Sign up to set email alerts
|

Beyond depression and anxiety; a systematic review about the role of corticotropin-releasing hormone antagonists in diseases of the pelvic and abdominal organs

Abstract: Evidence for beneficial effects of corticotropin releasing hormone (CRH) antagonists in abdominal and pelvic organs is emerging in preclinical studies. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement a compilation of preclinical studies using CRH receptor antagonists as a treatment for abdominal and pelvic disease was carried out. The Animal Research: Reporting of In Vivo Experiments (ARRIVE) essential 10 guidelines were used to determine quality of the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…The low level of IL-10 in colon patients may be due to a genetic disorder and genetic defects in the IL-10 / IL-10R pathway, as they develop acute early colitis [64]. This indicates that IL-10 plays an important role in maintaining the normal immune tolerance of the gut and that its reduction causes immune disturbance and inflammation that may lead to symptoms of IBS [65].As for the comparison among age groups of people with irritable bowel syndrome, the results of the current study showed a statistically significant difference among them, as the age group (50-41) was the least significant, and this was in consistency with the study of [66,67] .The study of [66]included 108 patients with colon disorders divided into two groups of ages (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) and the duration of the disease was 6 years. The reason for this may be the abnormal immune regula...…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The low level of IL-10 in colon patients may be due to a genetic disorder and genetic defects in the IL-10 / IL-10R pathway, as they develop acute early colitis [64]. This indicates that IL-10 plays an important role in maintaining the normal immune tolerance of the gut and that its reduction causes immune disturbance and inflammation that may lead to symptoms of IBS [65].As for the comparison among age groups of people with irritable bowel syndrome, the results of the current study showed a statistically significant difference among them, as the age group (50-41) was the least significant, and this was in consistency with the study of [66,67] .The study of [66]included 108 patients with colon disorders divided into two groups of ages (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) and the duration of the disease was 6 years. The reason for this may be the abnormal immune regula...…”
Section: Discussionsupporting
confidence: 83%
“…The current study showed that the high level of interleukin-8 in patients with irritable bowel may have a major role in the pathogenesis of the disease, as irritable bowel syndrome (IBS) was previously considered a psychosomatic disorder, but recent studies such as [22,23]. indicated that inflammation plays an important role in colon irritation, as the studies confirmed changes in Mast cell (MC), T lymphocytes and B lymphocytes, and showed higher concentrations of cytokines in the colon mucosa and in the blood of patients with Irritable Bowel Syndrome, compared to healthy subjects [24].…”
Section: Discussionmentioning
confidence: 86%
“…1 to 10% risk of metabolic disorders [25]. 16.9% to 22.9% risk of gastrointestinal disturbance [26].…”
Section: Sertralinementioning
confidence: 99%
“…They have yet brought plenty of problems, such as high affinity, long elimination half-life, active metabolites, high protein binding, pre-clinical screening, mismatch between dynamic characteristics of CRHR function and subject patients, acute versus advanced manifestations of the disease; NBI-77860 has the side effect of headache; R121919 significantly reduces the score of depressive patients, but the relevant study lacks blind, randomized, or placebo-controlled controls and causes elevated liver enzymes; there was no significant difference between CP-316,311 and placebo treatment. 119 - 121 In addition, the balance between receptor affinity and the pharmacokinetic property of CRHR1 antagonists remains the focus of the pharmaceutical industry. 114 Besides, CRHR2 agonists have an anti-anxiety effect in CNS, but can delay gastric empty, therefore, organ-selective CRHR2 agonists should be chosen in clinic.…”
Section: Crh-related Treatmentmentioning
confidence: 99%